Pembelajaran Maharatul Istima dengan Menggunakan Media Youtube di Pondok Pesantren Raudhatul Muta’allimin II Tanggamus - Sya'bani, Muhammad Zaky; Sutopo, Langgeng; Asriyah, Masfiyatul; Ramadhan, Habib Eka; Pasahi, Said Farid; Nurkholis (Al Mufid, 2023)
The application of Arabic language learning today has many difficulties both from the component of language skills and language elements, this happens because of the lack of discussion related to strategies, models, learning methods that are in accordance with learning Arabic which is a foreign language. Arabic language learning in general has been taught at the Raudhatul Muta'allimin 2 Tanggamus Islamic Boarding School but very rarely the practice of learning listening skills. Meanwhile, listening skills are the first thing that must be taught in the language learning process. The purpose of this activity is assistance in the application of listening skills learning using Youtube media. The result of the analysis of the results of this activity is an increase in students' courage and motivation in practicing Arabic in shaping the language environment. The increase in students' understanding and motivation can be seen from the ability of students to apply speaking about sentences in learning. It can be concluded that learning listening skills using Youtube media is effective to increase courage and motivation to practice Arabic in everyday life.